Take-over announcements and insider trading activity on the Johannesburg Stock Exchange - N. Bhana (South African Journal of Business Management, 1987)
The objective of this study was to carry out an investigation into the abnormal return behaviour of a sample of 50 acquired companies on the Johannesburg Stock Exchange during the period 1976-1985. Insiders appear to take market positions on prospective take-overs approximately 40 trading days before the announcement, and there appears to be uncontrolled abuse of insider trading rules in the 15 days immediately prior to the take-over announcement date. Legally defined insiders were not responsible for the abuse of inside information relating to the proposed take-overs. It would seem that substantial insider trading is carried out through third parties in order to escape detection of the authorities. The JSE appears to be inefficient in reacting to the public announcement of a planned take-over, and Section 233 of the Companies Act which regulates insider trading in South Africa is clearly ineffective. Various deficiencies and loopholes in the existing legislation are identified and recommendations for amendments are suggested.
Keywords: 650